On the Fringes of the Classless Society: Notes on Constantin Stoiciu’s Film Scripts. - Toderici, Radu (Caietele Echinox, 2020)
Focusing on the film scripts of the lesser-known, but prominent writer and film official Constantin Stoiciu, this essay assesses his contribution to the shared cinematic imaginary of the late ’60s and ’70s Romanian cinema and delineates the main strategies he resorted to in order to insert two of his thematic obsessions, class differentiation and class anxiety, into his narratives penned for the big screen.